A Multi-Level Explanation of Mass Support for the Judiciary. (2nd July 2016) - Walker, Lee Demetrius
ABSTRACT: Predispositions about regime type affect individuals' support for the judiciary on both the individual and the group level. I also show that the level of judicial independence affects public support for the judiciary in countries with dependent judiciaries, but the effect of judicial independence is conditioned by the predisposition that people have toward regime type. I show that judicial independence affects both (1) diffuse support and (2) specific political support for the judiciary. In particular, judicial independence has a positive effect on the diffuse support of liberal democrats. Meanwhile, delegative democratic specific political support is significantly higher than the specific political support of liberal democrats and authoritarians. Taken together, findings suggest that liberal democrats and delegative democrats support majoritarian governance in such a manner that judiciaries may promote certain decisions to these important constituents in the courts interactions with the executive and legislature.